Adipose Tissue-Derived Mesenchymal Stem Cells as a Potential Restorative Treatment for Cartilage Defects: A PRISMA Review and Meta-Analysis - Henry Yue-Hong Meng; Victor Lu; Wasim Khan (MDPI AG, 2021)
Cartilage defects are a predisposing factor for osteoarthritis. Conventional therapies are mostly palliative and there is an interest in developing newer therapies that target the disease's progression. Mesenchymal stem cells (MSCs) have been suggested as a promising therapy to restore hyaline cartilage to cartilage defects, though the optimal cell source has remained under investigation. A PRISMA systematic review was conducted utilising five databases (MEDLINE, EMBASE, Cochrane Library, Scopus, Web of Science) which identified nineteen human studies that used adipose tissue-derived MSC (AMSC)-based therapies, including culture-expanded AMSCs and stromal vascular fraction, to treat cartilage defects. Clinical, imaging and histological outcomes, as well as other relevant details pertaining to cartilage regeneration, were extracted from each study. Pooled analysis revealed a significant improvement in WOMAC scores (mean difference: −25.52; 95%CI (−30.93, −20.10); p < 0.001), VAS scores (mean difference: −3.30; 95%CI (−3.72, −2.89); p < 0.001), KOOS scores and end point MOCART score (mean: 68.12; 95%CI (62.18, 74.05)), thus showing improvement. The studies in this review demonstrate the safety and efficacy of AMSC-based therapies for cartilage defects. Establishing standardised methods for MSC extraction and delivery, and performing studies with long follow-up should enable future high-quality research to provide the evidence needed to bring AMSC-based therapies into the market.